Pembelajaran Agama Islam Melalui Bermain Pada Anak Usia Dini - Mohammad Fauziddin (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2016)
The problem is how the singer hearts Research Planning Process Execution Yang achieved commercial articles hearts Islam Learning through Play in Nurul Islam TKIT Pare. While the purpose of describing the study to review and analyze the planning process, describe and analyze the Implementation Process and to review and analyze the findings describe Islam Learning through Play in Nurul Islam TKIT Pare. Research Methods The study is descriptive analysis method CASE WITH qualitative approach. Researcher as an instrument. Data retrieval techniques through observation, interview and document study. Tools Data Retrieval using Recorder tool, Manual Observation cameras and digital Based Research found that learning Islam through Playing in TKIT Nurul Islam, the Planning Process Learning has dilaksakan accordance WITH rules Planning, Learning Process Also has accordance WITH Principles of Child Development articles commercially Learning Yang Progress achieved ASPECTS OF SUCCESSFUL optimize religious moral Son. Based on these findings, then recommended: (1) the principal should improve Teacher Competence and Media Education, (2) Institute TK Neighbourhood should adopt a singer as prayer One alternative learning Appropriate WITH characteristics of Early Childhood, (3) Governments should organize training Learning through play approach, and (4) Researchers should examine ASPECTS Further development of the other to review developed